Historical retrospective of development of category "capital» - Назаренко, І. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article is based on the urgency and necessity of study of the conceptual apparatus of the category «capital» in retrospect. It investigates the origin of the term. The article lightes the approaches of scientists to the interpretation of the study definition. By the results of the study the Genesis of the views of representatives of economic thought on the interpretation of the category «capital» are examined and summarized. For in-depth understanding of capital it is reviewed and grouped the types of capital that are used by scientists.It is investigated the terms with which the representatives of the history of economic doctrines identified capital. It is set in the article the results of the study will contribute to a deeper understanding of the development and interpretation of the category "capital".